1, 7‐Bis(4‐hydroxyphenyl)‐4‐hepten‐3‐one from Betula platyphylla induces apoptosis by suppressing autophagy flux and activating the p38 pathway in lung cancer cells. (11th September 2019) - Jung, Hyun Jin; Song, Kyung‐Sik; Son, Youn Kyoung; Seong, Je Kyung; Kim, Sun Yeou; Oh, Seung Hyun
Abstract : Betula platyphylla (BP) is frequently administered in the treatment of various human diseases, including cancers. This study was undertaken to investigate the pharmacological function of the active components in BP and the underlying mechanism of its chemotherapeutic effects in human lung cancer cells. We observed that BP extracts and 1, 7‐bis(4‐hydroxyphenyl)‐4‐hepten‐3‐one (BE1), one of the components of BP, effectively decreased the cell viability of several lung cancer cell lines. BE1‐treated cells exhibited apoptosis induction and cell cycle arrest at the G2/M phase. Further examination demonstrated that BE1 treatment resulted in suppression of autophagy, as evidenced by increased protein expression levels of both LC3 II and p62/SQSTM1. Interestingly, the pharmacological induction of autophagy with rapamycin remarkably reduced the BE1‐induced apoptosis, indicating that apoptosis induced by BE1 was associated with autophagy inhibition. Our data also demonstrated that BE1 exposure activated the p38 pathway resulting in regulation of the pro‐apoptotic activity. Taken together, we believe that BE1 is a potential anticancer agent for human lung cancer, which exerts its effect by enhancing apoptosis via regulating autophagy and the p38 pathway.